Ability adversity quotient and mathematical literacy using the cooperative, integrated learning model, reading, and composition (CIRC) - Suri, Indah Resti Ayuni; Netriwati, Netriwati; Rahmawati, Rini (Fakultas Tarbiyah dan Ilmu Keguran IAIN Metro, 2025)
Previous research has implemented the adversity quotient and mathematical literacy, but none has combined it with the CIRC learning model. This research aims to determine the influence of the CIRC learning model on students' adversity quotient and mathematical literacy abilities—the research population at SMP Amal Bakti in South Lampung. The quasi-experimental research design uses random samples. Data instruments were collected through mathematical literacy tests and adversity quotient questionnaires. The prerequisite tests are the normality test and homogeneity test, and the hypothesis test uses the Multivariate Analysis of Variance (Manova) test with a significance level of 0.05. In the results of the analysis, it was found that there is an influence on adversity quotient and mathematical literacy abilities using the Cooperative, Integrated, Reading, and Composition (CIRC) learning model.